Methods for designing strategic narratives in the description of the 2022 Russian-Ukrainian war in documentaries - Rosinska, Olena; Tymińska, Marta (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses methods of designing strategic narratives in teledocumentaries created by various production teams and distributed through the YouTube platform. The authors underline the important role of teledocumentaries in creating an emotional and intellectual response to geopolitical topics among television viewers and attempt to analyse six documentaries focusing on the current war in Ukraine. The aim of the research was to determine key narrative patterns that are presented by production teams from various countries in the context of the armed aggression of the Russian forces in Ukraine. From this research, we can outline three main narrative templates: identity issues (“Us” vs. “Them”), temporal cognition and feeling of “stopping the time”, the image of enemy inter-twined with death, unforgiveness and fear.